Audiomagnetotelluric survey at the Bañitos-Gollete geothermal area, main andes cordillera of San Juan, Argentina - Barcelona, Hernan (2019)
The present research explores the Bañitos-Gollete geothermal field located in the Frontal Andes Cordillera over the Pampean flat-slab. We carried out an audiomagnetotelluric survey in order to define the underground geoelectrical structure and to understand the link between the geothermal fluid flow path and the main geological structures. 2-D audiomagnetotelluric models suggest that the deep-rooted N-S fault system controls the geothermal flow path. We propose a conductive heat-driven system, taking into consideration the geologic setting and the supposed low geothermal gradient of this tectonic environment. The mature Na-Cl waters from Gollete and an estimated reservoir temperature of ~140°C are consistent with this conceptual model. Further investigations are required to assess the geothermal potential of the study area, and the present work likely represents only the first but necessary step in the exploration process.